2020
DOI: 10.1371/journal.pone.0230838
|View full text |Cite
|
Sign up to set email alerts
|

Women’s body odour during the ovulatory phase modulates testosterone and cortisol levels in men

Abstract: A growing body of evidence suggests that men may perceive women's bodily odour to be more attractive during the high-fertility ovulatory phase than during other phases in the menstrual cycle. In particular, women's bodily odour may influence important aspects of male mating behaviour, but the precise nature of this phenomena remains to be elucidated. Twenty-six men and five women participated in the study. Each woman wore a cotton Tshirt during the night for 3 days during the ovulatory phase, after which the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Later studies found that odors of women in the late follicular phase accelerated the secretion of luteinizing hormone in recipient women [469]. Odors of women in the ovulatory phase also had influences on the secretion of testosterone in men [470,471], showing that the physiological conditions of both sexes are under the control of odors of others. Studies on behaviors [472] and the brain [473,474] have shown that influences of odors can happen at even subliminal levels [473] and in a reciprocal way [474].…”
Section: Phytochemicals For Neuropharmacological Effectsmentioning
confidence: 99%
“…Later studies found that odors of women in the late follicular phase accelerated the secretion of luteinizing hormone in recipient women [469]. Odors of women in the ovulatory phase also had influences on the secretion of testosterone in men [470,471], showing that the physiological conditions of both sexes are under the control of odors of others. Studies on behaviors [472] and the brain [473,474] have shown that influences of odors can happen at even subliminal levels [473] and in a reciprocal way [474].…”
Section: Phytochemicals For Neuropharmacological Effectsmentioning
confidence: 99%
“…Furthermore, the authors found that men's testosterone and cortisol levels could respond to both odours from fertile or ovulating women 10 . Many studies have documented this aphrodisiac character of the human vulvar and axillary odour, stimulating men's sexual interest in unique contexts 10,11 . Such claims have raised curiosity about whether vaginal dabbing could be a scientific measure of sexual attraction in humans.…”
Section: Introductionmentioning
confidence: 99%
“…10 Many studies have documented this aphrodisiac character of the human vulvar and axillary odour, stimulating men's sexual interest in unique contexts. 10,11 Such claims have raised curiosity about whether vaginal dabbing could be a scientific measure of sexual attraction in humans. Hence, the first step is to search for documentary evidence to that effect.…”
Section: Introductionmentioning
confidence: 99%
“…For skin gas sampling, we used a recently developed technique termed Passive Flux Sampler (PFS) [ 20 ]. It has been reported that PFS reduces the time of sampling and physical burden on subjects undergoing skin gas collection [ 17 , 21 , 22 ] compared with the other methods of sample collection [ 15 , [23] , [24] , [25] ]. We sought to address the following questions:…”
Section: Introductionmentioning
confidence: 99%